Assessment of school resilience in disasters: A cross-sectional study - Samaneh Mirzaei; Hossein Falahzade; Leila Mohammadinia; Khadijeh Nasiriani; Abbas Ali Dehghani Tafti; Zohreh Rahaei; Hamid Reza Amiri (Wolters Kluwer Medknow Publications, 2020)
BACKGROUND AND OBJECTIVES: School resilience is defined as risk-reducing strategies used to create a safe environment for students when faced natural disasters. Resilient schools, in addition to their educational role, provide a suitable capacity for responding to disasters and rehabilitation after the incidence. This study determined the level of disaster resilience of schools in Yazd, central Iran. MATERIALS AND METHODS: This is a descriptive-analytic study conducted among 400 schools and 367 participants in Yazd, 2018. To collect data, we used the school resilience in disasters questionnaire (α =0.95 and intraclass correlation coefficient = 0.97 [95% confidence interval: 0.96-0.98]) containing 48 questions. We also analyzed the gleaned data through the Pearson correlation coefficient, one-way ANOVA, and independent t-test. RESULTS: The total score of school disaster resilience was 153.30 ± 29.57. In these schools, the function had the highest (47.76 ± 13.96), and safety had the lowest (6.74 ± 3.18) score among all areas of school disaster resilience. There was a positive significant correlation between total resilience and areas of function, education, structural, nonstructural, architecture, commute routes, safety, location, and equipment (P < 0.001). Location had the smallest (r = 0.424) and function had the greatest (r = 0.854) correlation with total resilience. CONCLUSION: It can help the school management board in assessing the level of resilience of their school and determining the priorities for disaster risk reduction. Awareness of the status of resilience can help policy-makers and experts create an effective program for increasing resilience.